221 SECOND ALLOGENEIC BONE MARROW TRANSPLANT IN A CHILD WITH SICKLE CELL DISEASE USING A REDUCED-INTENSITY CONDITIONING REGIMEN AS A 'BOOST' FOR PROGRESSIVELY DECREASING DONOR CHIMERISM. Issue 1 (1st January 2007) - Majumdar, S.; Robinson, A.; Files, J.; Megason, G. C.
Abstract : Hematopoietic stem cell transplantation provides the only curative potential for sickle cell disease and has been shown to have an excellent outcome. Myeloablative conditioning regimens consisting of busulfan and cyclophosphamide, with or without antithymocyte globulin or total lymphoid irradiation, have been effective but are limited by increased toxicity. Reduced-intensity conditioning regimens have been shown to induce stable mixed chimerisms with amelioration of the complications from sickle cell disease, with the added advantage of reduced transplant-related toxicity. Both regimens, however, risk graft rejection and subsequent recurrence of sickle cell disease. We describe a 6½-year-old black male with hemoglobin SS disease who at the age of 4 years had an allogeneic BMT from an HLA-matched sibling sickle cell trait donor. Prior to BMT, the patient had a history of recurrent hospitalizations for pneumonia, dactylitis, and acute chest syndrome requiring prolonged mechanical ventilation. Conventional myeloablative conditioning regimen consisting of busulfan, cyclophosphamide, and antithymocyte globulin was used prior to transplant. The PATIENT required multiple packed red blood cell and platelet transfusions during the hospital stay. Immunosuppressive therapy after BMT consisted of prednisone and cyclosporine, which was gradually weaned over a 5-month period. The patient had minimal symptoms of graft-versus-host disease (GVHD). Chimerism studies followed closely over time have shown an inevitable gradual decline in the level of donor chimerism to 15%. Patient was given a donor lymphocyte infusion (DLI) 360 days after BMT, which showed no improvement of donor chimerism. Subsequently, the patient received another BMT from the same matched sibling with a reduced-intensity conditioning regimen consisting of fludarabine, melphalan, and campath. The patient tolerated the regimen exceptionally well. The patient is now on tapering immunosuppressive therapy consisting of mycophenolate mofetil and is without symptoms of GVHD. Follow-up chimerism studies at day 122 show 97% donor cells. This case shows that after closely weighing the risks and benefits, patients with hemoglobin SS disease may tolerate a second allogeneic BMT using a nonmyeloablative reduced-intensity conditioning regimen to 'boost' the donor chimerism level.